SCL/TAL1 cooperates with Polycomb RYBP-PRC1 to suppress alternative lineages in blood-fated cells - Chagraoui, H; Kristiansen, MS; Ruiz, JP; Serra-Barros, A; Richter, J; Hall-Ponselé, E; Gray, N; Waithe, D; Clark, K; Hublitz, P; Repapi, E; Otto, G; et al. (Springer Nature, 2018)
During development, it is unclear if lineage-fated cells derive from multilineage-primed progenitors and whether active mechanisms operate to restrict cell fate. Here we investigate how mesoderm specifies into blood-fated cells. We document temporally restricted co-expression of blood (Scl/Tal1), cardiac (Mesp1) and paraxial (Tbx6) lineage-affiliated transcription factors in single cells, at the onset of blood specification, supporting the existence of common progenitors. At the same time-restricted stage, absence of SCL results in expansion of cardiac/paraxial cell populations and increased cardiac/paraxial gene expression, suggesting active suppression of alternative fates. Indeed, SCL normally activates expression of co-repressor ETO2 and Polycomb-PRC1 subunits (RYBP, PCGF5) and maintains levels of Polycomb-associated histone marks (H2AK119ub/H3K27me3). Genome-wide analyses reveal ETO2 and RYBP co-occupy most SCL target genes, including cardiac/paraxial loci. Reduction of Eto2 or Rybp expression mimics Scl-null cardiac phenotype. Therefore, SCL-mediated transcriptional repression prevents mis-specification of blood-fated cells, establishing active repression as central to fate determination processes.